The persistence of non-tariff measures in ASEAN a question of compliance - Hirang, Gemelee G. (Philippine Law Journal, 2019)
While various treaties and agreements have substantially reduced tariff rates on most traded goods, international trade is still burdened by restrictive laws and regulations. As a result, policymakers have shifted their focus to non-tariff measures ("NTMs") which have the potential to adversely affect trade flows. One such example is the Association of Southeast Asian Nations' (ASEAN) efforts to harmonize and reduce non-tariff measures, as well as eliminate non-tariff barriers, all of which are embodied in both treaty and soft law commitments. Nevertheless, these measures have persisted, and even increased, in ASEAN during the past decades.